Electrochemical biosensors based on laser induced graphene to detect foodborne pathogens in food - Soares, Raquel Rainier Alves (2019)
With the sharp increase in the world population, the demand for food production with an efficient quality control has grown substantially, since foodborne diseases and contaminations still considerably impact society. Therefore, there is a serious need for rapid, easy handling, sensitive and inexpensive biosensor devices, considered to be an excellent alternative to monitor food quality. Linked to this, researches on materials that are eco-friendly, easy to obtain, simple handling and widely applicable have become increasingly present in the scope of innovation and developmentofnew products, such as graphene. In this context, the objective of this work is to develop electrochemical biosensors based on graphene produced by laser induction, incorporated with specific antibodies to detect Salmonella enterica, and to apply them on food. Firstly, porous graphene electrodes were obtained by Laser-Induced Graphene (LIG) and evaluated according to its morphology, electrical conductivity, charge transfer ability, and graphene formation quality. The characterization techniques employed were: Scanning Electron Microscopy, Cyclic Voltammetry, Raman Spectroscopy and X-Ray Diffraction (XRD). The electrodes displayed good electrochemical performance, and were sequentially incorporated with antibodies, thus obtaining immunosensors. These devices showed excellent ability to detect pathogenic bacteria in food using the Electrochemical Impedance Spectroscopy technique, which represents an important advance in the field of food safety. Finally, the selectivity of the immunosensor was also tested in food using another inoculated pathogen, Escherichia coli, under the same conditions, playing the role ofa negative control. Considered a highly promising device that can be easily produced, the developed impedimetric immunosensor has unique properties that make it a viable option for pathogen detection in food, and an excellent alternative for electrochemical sensors that are directly induced onto the film.